Improvement of Soil Chemical Properties and Growth of Maize due to Biochar Application on Ultisol - Rianida Taisa; Desi Maulida; Abdul Kadir Salam; Muhammad Kamal; Ainin Niswati (UNIVERSITY OF LAMPUNG, 2019)
Ultisols have poor soil characteristics, yet biochar is one of the technologies that can be applied as a soil enhancer to improve the soil quality. Biochar has succeeded in improving soil quality, through improving soil physical, chemical, and biological properties. This research aimed to improve the quality of soil chemical properties and growth of maize plant, as well as to find a combination between biochar type and dosage of biochar that is able to improve the chemical properties of Ultisols and/or the growth of maize plant. This research was conducted at the Greenhouse and Soil Science Laboratory, Faculty of Agriculture, University of Lampung. This study used a randomized block design (RBD) arranged in factorial with 3 factors and 3 replications. The first factor was the soil layer (topsoil and subsoil), the second factor was the type of biochar (biochar of cocoa shell and biochar of oil palm shell), and the third factor was the biochar dosage (0, 10%, 20%, and 30% of 10 kg of oven dry weight soil). The results showed that (1) the application of biochar from the cocoa shell and oil palm shell on Ultisols improved some parts of soil chemical properties, namely CEC, organic C, and Kexc, (2) application of biochar from the cocoa shell and oil palm shell on Ultisols increased the plant height, the number of leaves, and the dry weight of maize, (3) application of biochar from the cocoa shell at a dosage of 20% was significantly improved CEC of Ultisols (4) application of biochar from the cocoa shell in top soil at a dosage of 30% significantly improved the soil organic C of Ultisol, (5) application of biochar from cacao shell at a dosage of 30% was significantly improved Kexc, (6) application of biochar from oil palm shell at a dosage of 10% significantly increased maize plant growth.